Resources for Malacological Research in Orton Memorial Library of Geology - Regina Brown (Hello World!, 1974)
AIthough the Library's holdings encompass the entire range of geological research from the traditional fields of mineralogy and paleontology to lunar geology and environmental pollution, one of its strengths is molluscan literature. It is this segment of the collection we wish to discuss. A guide to information sources (bibliographies and other reference tools) prefaces a list of serial publications that publish molluscan research. Finally, we mention the general treatises and regional studies in the Orton Memorial Library collection.